SEMANTIC SYNCRETISM AS A REGULATOR OF DYNAMIC STABILITY IN THE LEXICAL SYSTEM OF A LANGUAGE - Marina Vas. Pimenova (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie)
The article aims to describe the peculiarities of historical evolution in the lexical-and-semantic system of the Russian language stipulated by the development of the phenomenon of syncretism – formal substantive linguistic asymmetry, which is noted to be insufficiently studied. The linguistic nature of a special lexical-andsemantic category (syncretsemia) reflecting the “insoluble” semantic syncretism is demonstrated. Doubt is expressed in the correctness of the “straightforward” model of semantic evolution presented by language historians as an axiom. It is argued that syncretism predetermines the development of lexical meaning in a “spiralwise” direction: syncretism – its transformation/fragmentation – syncretism at a new level of language development. The author characterizes some major stages in the process of syncretic meaning modification. They occur simultaneously with the shifts in particular phases in the development of thinking. It is noted that in the most ancient period the original semantic syncretism was “compressed” to a flat state in the meaning of the etymon (syncretic word), indivisibly indicating a number of concepts. The transformation of semantic syncretism through the narrowing-concretization of the syncretic meaning is presented simultaneously with the expansion of its lexical expression with the help of minimal units of the Old Russian text (syncretemes) based on metonymy. The paper introduces the examples of original syncretism fragmentation through the intensive formation of derivatives from the invariant etymon and the gradual assigning them some components of the originally syncretic meaning. The cases of “stretching” the original syncretic syncretemes are considered. New types of semantic syncretism are shown to arise at the new level of language development. Furthermore, a modern transformation of syncretic units is observed. Syncretism is proved to be a fundamental ontological condition for the evolutionary stability in the lexical system of a language.